Drivers of membrane fouling in the vanadium acetylacetonate flow battery - Rungta, R; Smith, KP; Monroe, CW (Elsevier, 2024)
Vanadium acetylacetonate (V(acac)3) disproportionation electrochemistry promises a crossover-tolerant, high-voltage flow battery, but exhibits low efficiency and short cycle life. We show that membrane fouling, rather than a parasitic side reaction, dominates early performance fade. Crossover rates through porous membranes were estimated from voltage transients with an adaptive observer while cycling flow-through reactors. For 0.1M V(acac)3 and 0.3M TEABF4 in acetonitrile flowed countercurrently at 5.0cms−1 parallel to the separator, fresh Daramic 175 and Celgard 4650 afforded active-species mass-transfer coefficients of 3.8μms−1 and 7.5μms−1, respectively, which decreased and became non-Fickian as cycling progressed. At ±10mAcm−2 from 0%–20% state of charge, voltage efficiency with Celgard fell from 96% to 60% over 27 cycles. Separator replacement restored the coulombic and voltage efficiencies, which repeated their first progression. Impedance spectra from series-connected canary cells reveal that separator resistances remain stable during open-circuit exposure to charged single electrolytes, but increase under applied current or open-circuit contact with differently charged electrolytes.